2019
DOI: 10.3389/fonc.2019.01327
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of Gastric Tumor Cell Index and Two-Drug Combination Therapy via 3-Dimensional High-Throughput Drug Screening

Abstract: Tumor heterogeneity greatly limits personalized treatment of cancer. Patient-derived tumor cell (PDC) models precisely recapitulate the molecular properties and biology of the disease, making them effective preclinical tools for assessing anti-cancer drug activities. Accurate estimation of tumor purity is essential for performing high-throughput drug screening (HTS). In the present study, we measured and predicted the tumor population index in PDC models for two-drug combinational strategies using HTS system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…TEER experiments and molecular interventions revealed that, at non-transfected conditions, GC-derived cell lines had lower electrical resistance values than their nontumoral counterpart GES-1 (TEER ranging from 26 to 62 Ω cm 2 ), with the only exception of MKN-74 cells, which have noticeably higher TEER levels (from 140 to 230 Ω cm 2 ). This situation observed for AGS and MKN-45 cells are consistent with the high cell motility and EMT-induction profile defined by the aberrant nuclear vimentin distribution that has been described for both cell lines during a high-throughput analysis of gastric tumors for drug screening [56]. MKN-74 TEER levels can be explained considering their moderate differentiation grade, which gives them an epithelial-like phenotype, and their high P2Y2Rinduced proliferation rates [14], allowing them to reach 100% confluence after 24 h postseeding, giving them the electrical resistance pattern observed by us.…”
Section: Discussionsupporting
confidence: 88%
“…TEER experiments and molecular interventions revealed that, at non-transfected conditions, GC-derived cell lines had lower electrical resistance values than their nontumoral counterpart GES-1 (TEER ranging from 26 to 62 Ω cm 2 ), with the only exception of MKN-74 cells, which have noticeably higher TEER levels (from 140 to 230 Ω cm 2 ). This situation observed for AGS and MKN-45 cells are consistent with the high cell motility and EMT-induction profile defined by the aberrant nuclear vimentin distribution that has been described for both cell lines during a high-throughput analysis of gastric tumors for drug screening [56]. MKN-74 TEER levels can be explained considering their moderate differentiation grade, which gives them an epithelial-like phenotype, and their high P2Y2Rinduced proliferation rates [14], allowing them to reach 100% confluence after 24 h postseeding, giving them the electrical resistance pattern observed by us.…”
Section: Discussionsupporting
confidence: 88%
“…Combination index (CI) based on median effect analysis. 28 CI > 1, CI = 1, and CI < 1 indicate antagonism, addition, and synergy, respectively. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%